Pengaruh Fee Audit, Audit Tenure, Rotasi Audit Terhadap Kualitas Audit - Rika Indah Lestari; Mahameru Rosy Rochmatullah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the significance of the impact of audit fees, audit tenure, and audit rotation on audit quality in textile and garment subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022. The data used in this study are quantitative data sourced from secondary data, which is obtained from each company in the textile and garment subsector or from the official IDX website, www.idx.co.id. The population in this study consists of 22 textile and garment subsector companies. After the sample selection process, the final sample consists of 47 companies. The sampling technique used is total sampling. Data collection is conducted using secondary data in the form of financial statements and annual reports. The data analysis techniques employed include classical assumption tests, multiple linear regression analysis, t-tests, f-tests, and the coefficient of determination. The study's results indicate that audit fees significantly influence audit quality in textile and garment subsector companies, audit tenure does not significantly influence audit quality in textile and garment subsector companies and Audit rotation does not significantly influence audit quality in textile and garment subsect